The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.4172/2155-9880.1000368
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Dimensions and Functional Parameters in Nigerian Children with Homozygous Sickle Cell Anaemia Using Echocardiography

Abstract: Background: Sickle cell anaemia (SCA) is the most common and burdensome inherited disease affecting children in Africa. Nonetheless, there remains a paucity of literature from Nigeria about its effects on cardiac dimensions and functioning in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
2
5
1
Order By: Relevance
“…In this study, the left atrial and left ventricular internal dimensions, wall thickness and LV mass were significantly increased in SCD patients, though LV ejection fraction was similar in both groups. This finding is in keeping with findings from previous studies [13] enlargement and hypertrophy is compensatory mechanisms for the long standing volume overload. These cardiac changes are needed in patients with chronic anaemia to increase the cardiac output, with little increase in heart rate.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the left atrial and left ventricular internal dimensions, wall thickness and LV mass were significantly increased in SCD patients, though LV ejection fraction was similar in both groups. This finding is in keeping with findings from previous studies [13] enlargement and hypertrophy is compensatory mechanisms for the long standing volume overload. These cardiac changes are needed in patients with chronic anaemia to increase the cardiac output, with little increase in heart rate.…”
Section: Discussionsupporting
confidence: 93%
“…The inter-and intra-observer variability was calculated as (mean percentage errors) 13 . All measurements were compared with that of the standard population by calculating their z-scores [16][17][18] .…”
Section: Methods Of Assessing Cardiac Chambersmentioning
confidence: 99%
“…This study was carried out at the out-patient clinic of UNTH, Ituku-Ozalla, Enugu among children who were between 3 years and 18 years. This is because confounders such as increase biventricular pressure which is seen in children with sickle cell anaemia below the age of three years will affect the results [15][16][17] .…”
Section: Study Area/populationmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] The clinical manifestations of SCA are protean with multiorgan effects, including cardiovascular complications, which are recognized as signi cant contributors to morbidity in these children. [3,4] The structural integrity and contractile function of the left ventricle in children with SCA have received little research attention, and con icting ndings have been reported; [4][5][6][7] however, Rees et al [8] reported a signi cantly reduced left ventricular ejection fraction (LVEF) in children with SCA compared with controls in the USA, Chung et al [9] in Jamaica, and Bamigboye-Taiwo et al [10] in Nigeria found no signi cant difference between the two groups with respect to LVEF. Furthermore, the relationship between haemoglobin and foetal haemoglobin levels and left ventricular systolic function and geometric patterns in paediatric SCA patients has remained largely unexplored.…”
Section: Introductionmentioning
confidence: 99%